ANALISIS PENERAPAN MANAJEMEN WAKTU DENGAN METODE CPM PADA PROYEK PEMBANGUNAN PERUMAHAN DEWI KENCANA BLOK A KOTA MALANG - Setiawan, Agus; Koderi W.H., Muhammad; Rizky M, Zidan; Yuniar Caroline, Vanezia (SAINTIS Jurnal ilmu-ilmu eksakta, 2025)
The success of a project depends on the efficiency of its implementation, with clear objectives, a well-structured plan, and proper implementation. A good project estimation project will provide an estimate of time and cost; if you work on a project for a long period of time, the cost of completion will increase. A good one takes into account time and cost. If you work on a project for a long period of time, the cost of completion will increase. Project management is one of the factors that contributes to the success of a project in achieving its goals within a specified time period. Management is one of the factors that determines the success of a project in achieving its goals according to the specified time period. This study focuses on time management in the Dewi Kencana project in Block A, No: 29, Malang City. The Critical Path Method (CPM) is used for time management and to understand the critical path of a project. The data collection method is carried out by field studies using the interview method with the project head which contains data for further research. The results obtained from the study with the completion of forward calculations, backward calculations, free float and total float. The results of the project completion duration obtained were 23 weeks, 16 weeks faster than the project completion plan of 39 weeks.